Costa Rica : du petit pays « démocratique, sain et pacifique », au leader de l’écotourisme et de la protection de l’environnement - Nathalie Raymond (Études Caribéennes)
Costa Rica has become an essential reference point in terms of ecotourism and conservation of the environment over the past fifteen years. The country became famous for its original policy to preserve the environment. Approximately 27% of the country's land is protected and national parks cover more than 13% of the Costa Rican territory. An analysis of the Costa Rican approaches to the development of tourism, provides an example of the importance of political factors and the control of “image” in the popular and public imagination.